Levels of visual stress in proficient readers: Effects of spectral filtering of fluorescent lighting on reading discomfort - Loew, Stephen J.; Rodriguez, Celestino; Marsh, Nigel V.*; Jones, Graham L.; Nunez, Jose Carlos; Watson, Kenneth (Cambridge University Press, 2015)
Visual stress (VS) affects reading in 5–12% of the general population and 31–36% of children with reading disorders. Symptoms include print distortions and visual discomfort when reading, and are exacerbated by fluorescent lighting. Prior research has indicated that VS can also affect proficient readers. We therefore examined levels of visual discomfort in a group of expert readers (n = 24) under both standard and spectrally-filtered fluorescent lighting. Participants rated their awareness of six symptoms of VS under each lighting condition. Under the standard condition, 4(16.7%) of the group recorded moderate to high levels of VS. Differences in symptom levels and reading speed between conditions were analysed using the Wilcoxon Signed Rank Test. Under the filter condition, the group reported less discomfort regarding all six symptoms of VS surveyed. The differences were significant with respect to three of the symptoms (p = .029 - p < .001), with a medium effect size in all of them (r = .31 - r = .46) and total score (p = .007; r = .39). Variations in reading proficiency included significantly fewer self-corrections (p = .019) and total errors (p = .004). Here we present evidence that VS-type symptoms of reading discomfort are not confined to populations with reading difficulties and may also occur in proficient readers, and that simple adaptations to fluorescent lighting may alleviate such symptoms.